Teknologi Menyumbang Kepada Peningkatan Motivasi Pelajar - Intan Farahana Kamsin; Rosseni Din; Fariza Khalid; Nor Syazwani Mat Salleh; Analisa Hamdan; Siti Zuraida Abdul Manaf (Jurnal Dinamika Pendidikan dan Pembelajaran, 2015)
Awareness of the importance of education among Orang Asli students in Malaysia is still at a low level, and this has contributed towards the increase of truancy rate among them. Lack of motivation to attend school was one of the cause contributed to this problem. If these problems are not addressed, they will be left out of from the mainstream education in the State. Thus, this study aims to explore how the Information Technology and Communication (ICT) program can increase their motivation to study. For this study, case studies used which involve Orang Asli students as the unit of analysis. Interviews and observations were conducted to obtain detailed information with respect to the phenomenon being studied. The results show that, the integration of ICT program has contributed in increasing their motivation to attend school. In conclusion, the implemented of ICT program plays an important role in improving Orang Asli students' motivation to gain knowledge.